Advances and Patents about Medical Surgical Operation Bone Drilling Equipment - Yang, Min; Li, Changhe; Li, Benkai; Wang, Yaogang; Hou, Yali (Recent Patents on Mechanical Engineering, 2015)
With the increasing application of mechanical engineering in medical areas, bone drilling has become one essential part of orthopedic surgery. Recently, there are more and more researches and developments on bone drilling for fixing implants or widening operative field and related equipments. However, the uncontrollable axial force and over high drilling temperature during bone drilling not only influence drilling quality and loose the prosthesis implants, but also are easy to cause fracture nonunion and various operative complications, thus prolonging the recovery time. All existing drilling equipments employ manual feed and depend to a greater extent on the experiences of doctors. Doctors could judge whether bone has been drilled through precise judgment. Excessive feeding because of lack of clinical experiences or misjudgment during operation will cause secondary injuries to patients. Therefore, the author designed a surgical bone drill with controllable axial force. It uses abrasive particle drill, brazed PCBN superhard material drill, step drill and brazed twist drill. It could judge whether the bone has been cut through according to voltage signal collected by the intelligent integrated control system and thereby stop feeding automatically. Moreover, a theoretical analysis and experimental research on influencing factors of drilling temperature have been conducted to provide references for clinical practice. This paper analyzed advances and patents about medical surgical operation bone drilling equipment in recent years, including cranial drills, bone drills with drillings cleaner, drilling depth adjustable bone drills, automatic stop bone drills and other bone drills.
Keywords: bone drills with drillings cleaner